Comparative Study of Dezocine and Ketorolac Tromethamine in Patient-Controlled Intravenous Analgesia of Laparoscopic Cholecystectomy - Ying, Yidan; Fei, Shuke; Zeng, Zhiying; Qu, Xiaoyong; Cao, Zemin (Frontiers in Surgery, 2022)
Purpose: To observe the application value of dezocine and ketorolac tromethamine in patient-controlled intravenous analgesia (PCIA) of patients undergoing laparoscopic cholecystectomy (LC). Methods: 154 patients who underwent LC surgery in our hospital and received PCIA after surgery from September 2020 to September 2021 were selected, they were divided into group A (n=77) and group B (n=77). The group A was given dezocine, group B was given ketorolac tromethamine. The analgesia, sedation, comfort and adverse reactions of the two groups were closely observed at 4h, 8h, 12h and 24h after surgery. Results: At 4h, 8h, 12h and 24h after surgery, the visual analogue scale scores in group B were lower than those in group A (P<0.05). At 4h, 8h, 12h and 24h after surgery, the Ramsay scores in group B were higher than those in group A (P<0.05). At 4h, 8h, 12h and 24h after surgery, there was no significant difference in Bruggrmann comfort scale scores between the two groups (P>0.05). There was no significant difference in the incidence of adverse reactions between the two groups (P>0.05). Conclusion: Both dezocine and ketorolac tromethamine have high clinical application value in patients who underwent LC surgery and received PCIA, with higher patient comfort and less adverse reactions. But compared with dezocine, ketorolac tromethamine can achieve better sedative and analgesic effects, which is worthy of clinical promotion.